International trade and firm performance: A survey of empirical studies since 2006 - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
The literature on international trade and firm performance grows exponentially. This paper attempts to summarize what we learn from this literature to guide both future empirical and theoretical work in this area, and public debates and policy makers, in an evidence-based way. The focus is on the empirical part of the literature that consists of recently published papers using data for firms from manufacturing or services industries to study the links between international trade (exports and imports) and dimensions of firm performance (productivity, wages, profitability and survival). It discusses recent add-ons to the box of tools for empirical investigation in this field and suggests topics for future research.
Keywords: F14; 330; international trade; firm performance; empirical studies; survey; Außenwirtschaft; Unternehmensentwicklung; Welt